Human Resource Management in Nepalese Commercial Banks - Joshi, Nirajan (Nepalese Journal of Business, 2024)
This study examines the importance of human resource management in Nepalese commercial banks. Employee productivity is selected as the dependent variable. The independent variables are recruitment and selection, employee participation in decision making, performance appraisal, training and development, salary/compensation and promotion. The primary source of data is used to assess the opinions of the respondents regarding recruitment and selection, employee participation in decision making, performance appraisal, training and development, salary/compensation and promotion in Nepalese commercial banks. The study is based on primary data with 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors associated with human resource management in Nepalese commercial banks.The study showed that recruitment and selection have a positive impact on employee productivity in context of Nepalese commercial banks. It indicates that better and unbiased recruitment process leads to increase in employee productivity. Similarly, employee participation in decision making has a positive impact on employee productivity. It implies that the employee participation in decision making leads to increase in employee productivity. Similarly, performance appraisal has a positive impact on employee productivity. It means that better the appraisal of performance of employee, higher would be the employee productivity. The study also showed that training and development has a positive impact on individual’s choice. It indicates that proper trainings and development programs helps in stimulating the employee productivity. Likewise, salary/compensation has a positive impact on employee productivity. It indicates that good salary motivates employees to be more productive. Furthermore, promotion has a positive impact on employee productivity. It indicates that promotion plays an important role in stimulating the productivity of an employee.